PERAN PENYIDIK PEGAWAI NEGERI SIPIL (PPNS) PERIKANAN DALAM PROSES PENEGAKAN HUKUM KASUS IUU FISHING DI INDONESIA - Freshty Yulia Arthatiani (Widyariset, 2014)
This study aimed at describing the role of Fisheries Civil Servant Investigators (PPNS) in the law process of Illegal, Unreported and Unregulated (IUU) fishing in Indonesia. It utilized a descriptive qualitative method to analyse the primary and secondary data, which had been collected through interviews, observations and FGDs from a purposively chosen sample with a juridis normative approach. Definitively, IUU fishing is the act of fishing within the Indonesian, other country’s jurisdiction, or the open waters without permit, not reported, and not regu- lated. The law No. 45 year 2009 concerning the amendment of Law No. 31 Year 2004 on Fisheries stated that there are three sorts of law enforcers who have the rights to conduct investigations on offense in the fisheries sectors: the Civil Servant Investigators, the Navy Investigating Officers and the National Police Investigators. Despite the fact that the Civil Servant Investigators have been playing an active role in the law enforcement, especially for the IUU fishing cases, the function has not yet been very effective due to the lack of inter-institution coordination as well as communication among the law enforcers. Hence, matching perception, investigation mechanism as well as enforcement among the law enforcers are of utmost importance to alleviate the effectiveness of combat against IUU Fishing in Indonesia.